Cost effectiveness of a pragmatic exercise intervention (EXIMS) for people with multiple sclerosis: economic evaluation of a randomised controlled trial. (July 2014) - Tosh, J; Dixon, S; Carter, A; Daley, A; Petty, J; Roalfe, A; Sharrack, B; Saxton, JM
Background: Exercise is a safe, non-pharmacological adjunctive treatment for people with multiple sclerosis but cost-effective approaches to implementing exercise within health care settings are needed. Objective: The objective of this paper is to assess the cost effectiveness of a pragmatic exercise intervention in conjunction with usual care compared to usual care only in people with mild to moderate multiple sclerosis. Methods: A cost-utility analysis of a pragmatic randomised controlled trial over nine months of follow-up was conducted. A total of 120 people with multiple sclerosis were randomised (1:1) to the intervention or usual care. Exercising participants received 18 supervised and 18 home exercise sessions over 12 weeks. The primary outcome for the cost utility analysis was the incremental cost per quality-adjusted life year (QALY) gained, calculated using utilities measured by the EQ-5D questionnaire. Results: The incremental cost per QALY of the intervention was £10, 137 per QALY gained compared to usual care. The probability of being cost effective at a £20, 000 per QALY threshold was 0.75, rising to 0.78 at a £30, 000 per QALY threshold. Conclusion: The pragmatic exercise intervention is highly likely to be cost effective at current established thresholds, and there is scope for it to be tailored to particular sub-groups of patients or services to reduce its cost impact.